Individuals who lived alone or with an unpaid carer approaching the end of life at 2001 and 2011 census in Scotland - Savinc, Jan; Atherton, Iain (Scottish Centre for Administrative Data Research, 2023)
The census provides invaluable information on Scotland’s population and linking it to other data enables analysis of specific groups to inform policy. The following briefing provides key findings relating to the availability of carers at home for those at the end of life.
Keywords: Covid-19; Death; Unpaid carer